The shell measurements that best describe sexual dimorphism in the spur-thighed tortoise Testudo graeca from Algeria: Sexual dimorphism in Testudo graeca - Hadj Aissa, Benelkadi; Rodríguez-Caro, Roberto C.; Amroun, Mansour; Graciá, Eva (Basic & applied herpetology, 2022)
Due to phenotypic plasticity and sex-biased selective pressures, intraspecific variation in tortoise morphology is usually assessed by studying sexual dimorphism. However, inferences may differ based on the choice of shell size measurements for analyses. In this work, we identified linear measurements that best describe sexual dimorphism for the spur-thighed tortoise Testudo graeca whitei. We assessed 34 carapace and plastron measurements in 67 individuals (24 males, 43 females) in a population at the natural Mergueb site located on the central limit of the Algerian steppe. Twenty-two out of 34 measurements significantly showed sexual size dimorphism in ANOVA tests. When analyzing sexual shape dimorphism with ANCOVAs, nine measurements showed no shared allometry with the measurements used as covariates to correct by size. Meanwhile, 17 out of the remaining 23 measurements showed significant differences in shape. PCA analyses similarly described T. graeca’s sexual dimorphism. In general, females tend to be bigger than males, especially in central scutes what is probably linked with clutch sizes commitments. On the other hand, males are larger-sized in anterior and posterior scutes, probably as a result of courtship, male fighting and copulation. Some of the analyzed measurements are revealed as being especially adequate for further studying the geographical variation of sexual dimorphism in Testudo graeca